Wayang Dan Nilai- nilai Etis: Sebuah Gambaran Sikap Hidup Orang Jawa - Kushendrawati, Selu Margaretha (Paradigma: Jurnal Kajian Budaya, 2011)
The Javanese wayang performance reflects some ethical values that express the attitudes and norms of the Javanese people. The wayang stories bring into focus some elements of the culture, such as customs, arts, way of life, mysticism, and religion. The characters of the wayang performance depict some ways of life and mind-sets of the Javanese of an understanding of the final destination of life, sangkan paraning dumadi, which is a longing to be united with God at the end of their life. Wayang performance is a high form of Javanese culture that needs to be preserved to sustain multiculturalism in Indonesia.